Effective Contribution of Sarva Shiksha Abhiyan In Inclusive Education For Children With Special Educational Needs: Examining the Impact of Sarva Shiksha Abhiyan on Inclusive Education for Children with Special Educational Needs (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Present study aimed to analysesthe functioning of Inclusive Education for the Children with Special Needs(CWSN) under Sarva Shiksha Abhiyan programme and to study the opinion of CWSNabout the effectiveness of the programme. It was hypothesized that there is asignificant contribution of Sarva Shiksha Abhiyan in Inclusive Education forthe Children with Special Needs (CWSN) in Haryana.  The sample of the present study consisted of15 government schools of Panipat District in Haryana randomly selected and 20CWSN students of these schools along with 10 resource teachers from 5 blocks ofPanipat District were taken as a sample of the present study. The student andresource teacher were selected on purposive basis. In this study twoquestionnaires were used to collect data. The investigator used simplepercentage method. From the findings of thepresent study it can be concluded that an appreciable effort that anappreciable effort has been taken by the government in the form of legislativepolicies for the disabled, such as NPE (1986) and POA, budgetary delegation,infrastructural inputs, facilities such as Aids and Appliances, scholarships,teaching and learning material (TLM), Resource rooms and human resources (RT’s). Majority of RT’s and CWSNstudents who participated in the present study feels that government has takenmany progressive steps. More innovative programmes, strategies and solutionshave to be formulated for fruitful results. Positive contribution bycommunity, NGO’s, government to bring an attitudinal change towards a disabledlot can result in a motivational progress in the concerned area.